Is Going Green Worth It? Assessing Fan Engagement and Perceptions of Athletic Department Environmental Efforts - Jonathan M. Casper; Michael E. Pfahl; Brian P. McCullough (Journal of Applied Sports Management, 2017)
The purpose of this study was to examine the extent to which environmentally themed activities within an intercollegiate sport context impact fan engagement. A total of 557 fans responded to an online survey measuring fan connection to the athletic department, environmental values, expectations for environmental activities, event and at home environmental behaviors, perceptions of profile enhancement, and recall of environmental sponsors and major initiatives. Results found that fans expected athletic department environmental action and they help with favorable perceptions about the athletic program and university and influenced at event and home behaviors. Cluster analysis identified two clusters based on high pro-environmental and low pro-environmental perceptions. The high proenvironmental cluster was skewed female, had lower connection to the athletic program, and had higher recall of official environmental sponsors and athletic initiatives. The results provide a fundamental and foundational understanding of how environmental activities impact fan engagement and the value of such efforts.
Keywords: Environment; intercollegiate athletics; fan behavior; cluster analysis